Management of pneumothorax in adults with cystic fibrosis. Issue 11 (November 1982) - Penketh, A R; Knight, R K; Hodson, M E; Batten, J C
Abstract : The histories of 243 adults with cystic fibrosis were reviewed; 46 had experienced one or more spontaneous pneumothoraces (18.9%), and seven had died of this complication. There was a high incidence of recurrence on the same side after conservative management (50%) or intercostal drainage (55.2%). Prolonged intercostal drainage was associated with a high mortality. One-third of patients required surgical treatment. Twenty thoracotomies were performed. Three of these patients died but only two of the 17 survivors had recurrences. Severe airflow obstruction was not a contraindication to surgery. A plan of management for future cases is outlined.